DAMPAK EKSPETASI PELANGGAN, PERSEPSI KUALITAS, DAN PERSEPSI NILAI TERHADAP KEPUASAN PELANGGAN, SERTA IMPLIKASINYA PADA LOYALITAS PELANGGAN - A. J. Ibnu Wibowo; Fransisca Mulyono (Center for Economic Studies Universitas Katolik Parahyangan, 2009)
Service providers must deliver high-quality customer services that generate highly satisfied customers. In this article, we examine how customer expectation, perceived quality, and perceived value may lead to exceptional satisfied customers, and ultimately to customer loyalty. Specifically, we investigate the chain of events through which customer expectation, perceived quality, and perceived value influence customer satisfaction and customer loyalty in a sample of 323 customers. We present a conceptual model for linking customer expectation, perceived quality, and perceived value to customer satisfaction and customer loyalty, and test this model using structural equation modeling. The results suggest that (1) perceived quality and perceived value are linked to customer satisfaction; (2) customer satisfaction is linked with customer loyalty. Theoretical and practical implications of our findings are discussed.